Corporate Social Responsibility strategy for PT Pertamina Sungai Pakning community empowerment during the Covid-19 pandemic - dewi damaiyanti, Sherlly Dewi Damaiyanti (Universitas Ahmad Dahlan, 2022)
This paper aims to identify CSR analysis strategies at PT Pertamina Sungai Pakning in Community Empowerment during the Covid-19 Pandemic, especially in the section on community empowerment as social responsibility in the company. The method used in this study is qualitative with a description of the analysis to be able to provide an overview of the subject matter to be studied. The results of this study are corporate social responsibility activities in tackling the pandemic using three strategies, namely donations, capacity building and community empowerment. This third strategy is able to answer the needs of the community and encourage the establishment of synergy between companies and government agencies in efforts to overcome the pandemic. CSR during the Covid-19 pandemic has a great opportunity to release its best innovations in making meaningful social contributions as a form of long-term development on a balance between profitability and harmony with various stakeholders.